An analysis of the current framework for the exchange of taxpayer information, with special reference to the taxpayer in South Africa's constitutional rights to privacy and just administrative action - Möller, Louise (Department of Finance and Tax, 2016)
Internationally, as well as in South Africa, legal reform aimed at increasing taxpayer information transparency has gained momentum over the past few years, especially in the light of the G20 led Base Erosion and Profit Shifting ('BEPS') Project. Ensuring that the fundamental rights of the taxpayer, guaranteed by the Constitution1, remain protected amidst the hurried implementation of these reforms is of paramount importance and cannot be overlooked or deferred. To a great extent, the question as to whether the current rules, regulations, and practices surrounding exchange of taxpayer information in South Africa would pass constitutional muster has, as yet, gone unasked and unanswered in academic literature. This minor dissertation seeks to identify and analyse the constitutional questions raised by these existing rules and practices, with special reference to the constitutional rights of taxpayers in South Africa. Specifically, the current framework for both the automatic exchange of information and exchange upon request is considered in the context of two constitutional rights, namely the right to privacy and the right to just administrative action, with due recognition of the general limitation of rights provided for in the Constitution. Importantly, this paper does not dispute the need for exchange of taxpayer information in principle, nor the desirability of effective tax administration. It is furthermore appreciated and acknowledged that a balance must be struck between the often competing interests of the South African Revenue Service ('SARS') as an administrator seeking to discharge its mandate in the most efficient manner possible, and the fundamental rights of the taxpayer.